-92+9x=103-6x

Simple and best practice solution for -92+9x=103-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -92+9x=103-6x equation:


Simplifying
-92 + 9x = 103 + -6x

Solving
-92 + 9x = 103 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-92 + 9x + 6x = 103 + -6x + 6x

Combine like terms: 9x + 6x = 15x
-92 + 15x = 103 + -6x + 6x

Combine like terms: -6x + 6x = 0
-92 + 15x = 103 + 0
-92 + 15x = 103

Add '92' to each side of the equation.
-92 + 92 + 15x = 103 + 92

Combine like terms: -92 + 92 = 0
0 + 15x = 103 + 92
15x = 103 + 92

Combine like terms: 103 + 92 = 195
15x = 195

Divide each side by '15'.
x = 13

Simplifying
x = 13

See similar equations:

| 2y-9=4y+9 | | 5(x+3)=7x-21 | | q+10=-9q | | N^2+3n+c=0 | | 6(41-21)-6(20-3)= | | 14+h-14+h=30 | | 6q-8=5q | | 9k+8=K+14 | | 12ac-7c=5a | | 8w+5=4 | | -7-9j=-10j | | 12ac-7c= | | Y=4+6x-2x^2 | | -b=b+6 | | -4(5t-5)+3t=8t-4 | | 10(x+3)=4(2x+9)+4x | | 6x+10=4x+15 | | 3.3q-4.9-3.6q=-1.3q-5.3 | | G(x)=4n+16 | | 9=2(z-5)+3 | | 20-2x=100 | | 4b-3-7b-7= | | 7-3(y-2)=5(y-2)-4y | | 2n+1=4n-1 | | 0.2x+0.8=0.7x-1.7 | | 9=3(z+1) | | 3(1+11x)=0 | | -37=-3x | | 8k-7k=17 | | 27x^2-66x+24=0 | | 3x-x+7=15 | | y^2=14-5x |

Equations solver categories